Approach to Macrodactyly: A Case Report and Diagnostic Algorithm for Syndromic and Isolated Forms - Ioannis Kyriakidis; Iordanis Pelagiadis; Nikolaos Katzilakis; Eftichia Stiakaki (Pediatric Reports)
Background: Macrodactyly (megalodactyly or digital gigantism) is a rare condition of overgrowth affecting one or more fingers or toes. Methods: We report a case of a 16-year-old Caucasian male with macrodactyly, lipomas, nevi, dysmorphic features, and autism. The clinical suspicion for a Proteus-like syndrome was high. Results: Targeted PIK3CA, AKT1, and PTEN sequencing for the affected tissue was negative. Subsequent genetic testing revealed a 16p11.2 duplication along with a heterozygous pathogenic variant in PRRT2 (not causally associated with digit malformation). Conclusions: The clinical management of syndromic macrodactyly is well described by consensus guidelines, but isolated macrodactyly also needs pediatricians’ attention and warrants a multidisciplinary approach. After reviewing the literature, a diagnostic algorithm for the approach and differential diagnosis of macrodactyly is provided. Phenotypes associated with PI3K/AKT/mTOR pathway mutations (including PIK3CA-related overgrowth spectrum PROS) are described. Late effects, follow-up schedules, and surveillance for cancer are discussed.